Unmet health care service needs and caregiver needs of children with disabilities in Penang, Malaysia / Tan Seok Hong - Tan, Seok Hong (2016)
Unmet need for health services captures the degree to which needed health services are not received and is an indication of the difficulties experienced in the process of obtaining care. It is used to assess equity of access to health care across population subgroups. This study investigates whether current services are meeting the needs of children with disabilities and their caregivers in Penang, a state in Northern Malaysia. The objectives are to determine the magnitude of unmet service needs, as well as the child and family characteristics associated with these unmet needs. Problems faced by caregivers in getting access to needed services are identified. A cross-sectional population survey was conducted among caregivers of children with disabilities aged 0 – 12 years registered with the Penang Department of Social Welfare in 2012. Caregivers answered a self-administered mailed questionnaire which included an assessment of the child’s unmet need for 17 specific medical services and assistive devices, and a newly developed 20-item Caregiver Needs Scale (CNS). A total of 305 questionnaires were available for analysis (response rate 37.9%). Among the respondents, 41.3% had children with learning disability, 27.5% with multiple disabilities and 31.2% with sole visual, hearing, or physical disability. Distribution of total number of unmet needs revealed that 23.5% did not have any unmet needs and 76.5% had one or more unmet needs. More than 50% of children had unmet needs for dietary advice, psychology services, dental services, speech therapy, home nursing services, communication aids, home modifications, mobility aids and vision aids. Children with multiple disabilities, of younger age, with more severe disability and caregivers with higher education reported more needs. However, school age children were more likely to have higher level of unmet needs and having more than one disabled child was associated with less unmet needs. Level of unmet needs was not associated with severity of disability, ethnicity, education level and income level. Even though the result did not reach iv statistical significance, children with learning disability showed a tendency to have higher unmet needs compared to children with multiple disabilities. Overall, difficulties accessing services were mainly due to logistic problems, followed by issues related to skills and resources. Parent-provider relationship problems were least encountered. Caregivers needed the most help getting information and services for their child, followed by help with finances, help coping with the child, and lastly help getting child care. Caregivers of younger children and with more severe disability had more needs in all these domains. Besides that, caregivers of children with learning disability needed more help getting information and help with coping. Both caregivers of children with learning and multiple disabilities needed more help getting child care. Caregivers of Indian ethnicity, who had less than a tertiary education and who themselves had medical problems needed more help with finances. This study highlights the areas to prioritize in the provision and development of health services for children with disabilities in Malaysia, including support services for their families.